The three major antigens on the surface of Plasmodium falciparum merozoites are derived from a single high molecular weight precursor. - Anthony A. Holder; Robert R. Freeman (1984)
A 195,000 mol wt Plasmodium falciparum protein and processing fragments derived from it have been purified by monoclonal antibody affinity chromatography. A polyvalent antiserum has been raised against the purified protein and used to identify the terminal processing products associated with the merozoite. Three unique fragments of 83,000, 42,000, and 19,000 mol wt are present and they represent the major surface antigens of P. falciparum merozoites.